Haematogenous seeding in mycosis fungoides and Sézary syndrome: current evidence and clinical implications - Gniadecki, Robert; Guenova, Emmanuella; Querfeld, Christiane; Nicolay, Jan Peter; Scarisbrick, Julia; Sokol, Lubomir (British journal of dermatology, 2025)
Cutaneous T-cell lymphomas (CTCLs) are a heterogeneous group of diseases characterized by abnormal neoplastic T-cell growth in the skin. Mycosis fungoides (MF), the most common CTCL, manifests as erythematous skin patches and/or plaques, tumours or erythroderma. The disease may involve blood, lymph nodes and rarely viscera. Sézary syndrome (SS) is a unique leukaemia/lymphoma syndrome related to MF, which presents with blood and skin involvement at diagnosis.The pathogenesis of MF/SS is not fully elucidated. The presence of skin lesions at distant sites underpins a hypothesis that MF/SS lesions may develop through haematogenous seeding. Phenotypic similarities between malignant and normal T cells led to the notion that disease-initiating mutations occur in specific subtypes of mature T cells, which are responsible for most CTCLs. However, this mature T-cell precursor model is not always consistent with clinical observations and research on MF/SS pathogenesis.Here, we review evidence supporting an alternative model of pathogenesis for MF/SS involving haematogenous seeding as a key process responsible for the initiation and progression of the disease. According to this hypothesis, malignant transformation occurs at an early stage of T-cell development (probably in bone marrow or thymus), yielding circulating neoplastic T cells which colonize the skin where the microenvironment is most permissive for proliferation and evolution. These mutated precursor cells seed the skin where they find a suitable niche to develop into clinically perceptible disease. Subsequently, malignant T cells can re-enter the bloodstream, re-seed pre-existing lesions and seed new areas of the skin, causing synchronous and convergent changes in the transcriptomic profile of lesions and tumours, and clinical disease progression - ‘consecutive haematogenous seeding’ captures this temporal phenomenon.This model radically changes the current understanding of CTCL pathogenesis, transforming it from a primarily cutaneous disease with secondary involvement of blood, to a systemic disease, where the spread of malignant cells through the blood to the skin is not a phenomenon of advanced disease but is an essential component of pathogenesis.This understanding of MF/SS could have several clinical implications, including standardizing our approach to assessing blood tumour burden, potential advances in prognosis and monitoring, and investigating combination treatments to improve patient outcomes.Mycosis fungoides (or ‘MF’ for short) is a skin cancer caused by a type of immune cell called lymphocytes. People with MF develop patches, plaques and tumours on their skin. They can also develop widespread redness caused by the uncontrolled growth of lymphocytes. We thought that MF developed only from problems in lymphocytes in the skin. Recent research challenges this view and suggests that cells in the blood also play an important role in the development of MF.We introduce a new concept to explain MF. We suggest that cancer cells may develop in the immune system first, long before showing up in the skin. These cells can travel through the bloodstream and settle in the skin, where they grow more easily. Cancerous cells from skin lesions can also re-enter the bloodstream and move to new areas of the skin, spreading and worsening the disease.This research changes how we see MF. Rather than being a skin disease, it is a problem that affects the whole body. This could affect treatment by improving ways of detecting cancer cells in the blood, watching for disease changes and exploring treatments to help patients better.
Erstmals veröffentlicht: 15. November 2024
Gesehen am 28.07.2025